2006
DOI: 10.1194/jlr.m600001-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation-associated expression of ceramidase isoforms in cultured keratinocytes and epidermis

Abstract: Ceramides (Cers) accumulate within the interstices of the outermost epidermal layers, or stratum corneum (SC), where they represent critical components of the epidermal permeability barrier. Although the SC contains substantial sphingol, indicative of ceramidase (CDase) activity, which CDase isoforms are expressed in epidermis remains unresolved. We hypothesized here that CDase isoforms are expressed within specific epidermal compartments in relation to functions that localize to these layers. Keratinocytes/ e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
65
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 44 publications
8
65
0
Order By: Relevance
“…Until now, based on the physicochemical properties of these enzymes, the ceramidase activity has been considered to be restricted to the extracellular space. Moreover the strong increase in acidic ceramidase activity observed during keratinocyte differentiation is not paralleled by a similar change in acid ceramidase 1-encoding mRNA (69). Although this discrepancy has been tentatively explained by posttranscriptional modifications, it may also result from the expression of another acid ceramidase, i.e.…”
Section: Clip-170 Association With Lamellar Bodies Of Human Epidermismentioning
confidence: 77%
“…Until now, based on the physicochemical properties of these enzymes, the ceramidase activity has been considered to be restricted to the extracellular space. Moreover the strong increase in acidic ceramidase activity observed during keratinocyte differentiation is not paralleled by a similar change in acid ceramidase 1-encoding mRNA (69). Although this discrepancy has been tentatively explained by posttranscriptional modifications, it may also result from the expression of another acid ceramidase, i.e.…”
Section: Clip-170 Association With Lamellar Bodies Of Human Epidermismentioning
confidence: 77%
“…In situ hybridization revealed that ACER1 mRNA is highly expressed in the upper nucleated layers of the epidermis, but it is undetectable in the basal cell layer. In cell culture, ACER2 mRNA is markedly upregulated in epidermal keratinocytes by 1.2 mM extracellular calcium [112] or the combination of fetal bovine serum, Ca 2+ , and ascorbic acid [132]. These observations indicate that ACER1 may have an important role in the differentiation of epidermal keratinocytes.…”
Section: Alkaline Ceramidasementioning
confidence: 79%
“…In addition to cell survival, we recently demonstrated that AC mediates the differentiation of epidermal keratinocytes [112,132]. We showed that AC expression is increased during calciuminduced differentiation of epidermal keratinocytes [112,132], and RNAi-mediated knockdown of AC significantly inhibited the calcium-induced expression of keratin 1 and involucrin, two important proteins highly expressed in differentiated keratinocytes [112].…”
Section: Acid Ceramidasementioning
confidence: 91%
See 1 more Smart Citation
“…Cer hydrolysis, followed by sphingosine-to-sphingosine 1-phosphate generation. We previously reported that epidermal keratinocytes express all isoforms of ceramidase that have so far been characterized in mammalian species (46), suggesting that Cer can be hydrolyzed at/in ER/Golgi by alkaline ceramidase, in mitochondria and/or at the plasma membrane by neutral ceramidase, and in lysosomes by acidic ceramidase. We also recently demonstrated increases in Cer hydrolysis to sphingosine (followed by its conversion to sphingosine 1-phosphate) in keratinocytes in response to UV irradiation.…”
mentioning
confidence: 99%